2017
DOI: 10.1590/0034-7167-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hormonal contraceptives and the occurrence of stroke: integrative review

Abstract: Objective: To identify scientifi c evidence regarding the infl uence of hormonal contraceptive use and the occurrence of stroke. Method: Integrative review of the literature, through database search using the descriptors "contraceptive agents", "contraceptive devices", "contraceptives, Oral" and "Stroke". Original studies in Portuguese, Spanish and English, published in full and available online were included. Studies that did not answer our guiding questions and duplicated studies were excluded. Results: Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
0
10
0
19
Order By: Relevance
“…OCs are composed of synthetic hormones, such as estrogen and progesterone, which can be used isolated (progestogens) or in combination. Estrogen, notably Ethinyl estradiol, may cause important alterations in the hemostatic system, such as the 30-50% increase in the activity of procoagulant factors (factors II, VII, VIII, IX, X, XI, XII, XIII, and fibrinogen) [9], the reduction of natural anticoagulant factors (C-reactive protein, protein S, antithrombin) and the stimulation of endothelial dysfunction, which results in thromboembolic events such as DVT, PTE and CVA [1][2][3]9]. In addition to these hemostatic changes, those combined with higher doses of Ethinyl estradiol, such as the OC used by the patient, develop greater resistance to activated protein C (APC), higher levels of D-dimer, and changes in the lipid profile, such as increased LDL and total cholesterol [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCs are composed of synthetic hormones, such as estrogen and progesterone, which can be used isolated (progestogens) or in combination. Estrogen, notably Ethinyl estradiol, may cause important alterations in the hemostatic system, such as the 30-50% increase in the activity of procoagulant factors (factors II, VII, VIII, IX, X, XI, XII, XIII, and fibrinogen) [9], the reduction of natural anticoagulant factors (C-reactive protein, protein S, antithrombin) and the stimulation of endothelial dysfunction, which results in thromboembolic events such as DVT, PTE and CVA [1][2][3]9]. In addition to these hemostatic changes, those combined with higher doses of Ethinyl estradiol, such as the OC used by the patient, develop greater resistance to activated protein C (APC), higher levels of D-dimer, and changes in the lipid profile, such as increased LDL and total cholesterol [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In regards to CVA, 14 studies demonstrated that the use of OC increases the risk of this event, considered by the World Health Organization (WHO) a complication in primary care. Smoking, arterial hypertension, hypercholesterolemia, obesity, alcohol, migraine, and personal and family history of thrombotic diseases, are also factors implied in the increase of CVA incidence [3].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the influence of the use of hormonal contraceptives on the occurrence of Stroke, and found that smokers who used combined oral contraceptives presented 8.57 more chances and a greater relative risk (4.9) of Stroke when compared to the chance of non-smokers (3.1) or the relative risk of those who have never used this type of method (4.2) (13) .…”
Section: Discussionmentioning
confidence: 99%
“…For analysis and subsequent synthesis of the articles that met the inclusion criteria, a synoptic table was used to present data, also adapted and specially prepared for this purpose, including the following aspects: title of the research; authors’ name; intervention studied; results; recommendations; and conclusions 10 . It is noteworthy that during the elaboration of the clinical guideline, the levels of evidence and degrees of recommendation were used to classify the evidences found 11 .…”
Section: Methodsmentioning
confidence: 99%